Focused high frequency needle transducer for ultrasonic imaging and trapping - Hsu, Hsiu-Sheng (American Institute of Physics, 2012)
A miniature focused needle transducer (<1 mm) was fabricated using the press-focusing technique. The measured pulse-echo waveform showed the transducer had center frequency of 57.5 MHz with 54% bandwidth and 14 dB insertion loss. To evaluate the performance of this type of transducer, invitro ultrasonic biomicroscopy imaging on the rabbit eye was obtained. Moreover, a single beam acoustic trapping experiment was performed using this transducer. Trapping of targeted particle size smaller than the ultrasonic wavelength was observed. Potential applications of these devices include minimally invasive measurements of retinal blood flow and single beam acoustic trapping of microparticles.